Pengaruh ESG, Likuiditas, dan Struktur Modal Terhadap Kinerja Keuangan yang Dimoderasi Ukuran Perusahaan pada Perusahaan Sektor Healthcare Tahun 2020-2024 - Kurnia, Aliah; Desmiza, Desmiza (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the influence of ESG, liquidity, and capital structure on financial performance with company size as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This research is motivated by fluctuations in Return on Assets of healthcare sector companies post-pandemic and increasing attention to corporate sustainability practices. The study uses a quantitative approach with secondary data obtained from financial statements and sustainability reports of healthcare sector companies for the 2020-2024 period. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA) with the help of EViews 13. The results show that ESG has a negative effect on Return on Assets, while the Current Ratio and Debt to Equity Ratio have a positive effect on Return on Assets. Simultaneously, ESG, Current Ratio, and Debt to Equity Ratio have a significant effect on Return on Assets. Company size is unable to moderate the effect of ESG, Current Ratio, or Debt to Equity Ratio on Return on Assets. These findings indicate that the financial performance of healthcare companies is more influenced by internal factors than by moderating factors.